Performance of CMIP6 HighResMIP Simulations on West African Drought - Ajibola, Felix Olabamiji; Zhou, Botao; Shahid, Shamsuddin; Ali, Md. Arfan (Frontiers in Earth Science, 2022)
This article evaluated the performance of 7 CMIP6 HighResMIP models in the simulations of drought over two sub-regions of West Africa: the Guinea coast and Sahel during the historical period of 1985-2014, in terms of the potential evapotranspiration index (PET), climatic water availability (CWA), standardized precipitation evapotranspiration index (SPEI) at three time scale (i.e., 1, 3, and 12 months), and precipitation concentration index (PCI). The Climate Research Unit (CRU) TS v4.03 datasets were used as the observation reference. The observation shows that the PET and CWA during August (i.e., the rainfall annual peak) was less than 30 and 200 mm/month over the Guinea coast, respectively. The corresponding values over the Sahel were 100 and -50 mm/month. A significant decreasing trend was observed in drought over the Guinea coast (except Nigeria) and Sahel. The frequencies of extreme and severe droughts were observed respectively over Nigeria, Liberia and Sierra Leone during the historical period. The annual PCI from the observation indicated a moderate precipitation distribution over the Guinea coast and strong irregular distribution over Sahel. The 7 HighResMIP models show different behaviours in simulating all of above observation features. Among all the simulations, the ENSEMBLE, ECMWF, and IPSL generally perform better in almost all the statistical indices used although there are still biases that need to be resolved in the models.